The Relationship of Preeclampsia to the Incidence of Preterm Labor at Raden Mattaher Jambi Hospital in 2021-2023 - Quzwain, Suhair; Dewi, Hasna; Romadiani, Inaya (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
Objective: This study aims to determine the association between preeclampsia and preterm labor at Raden Mattaher Jambi Hospital. Methods: This study uses an observational analytic method with a cross-sectional. Data collection techniques using purposive sampling. Data were obtained from the medical records of all laboring mothers who met the inclusion and exclusion criteria. Result: There is an association between preeclampsia and preterm labor at Raden Mattaher Jambi Hospital from 2021 to 2023, with a p-value of